Low Friction Hull Coatings for Icebreakers. Phase II, Parts I and II. Laboratory and Field Tests. - Calabrese,S. J.; Peterson,M. B.; Ling,F. F. (1976)
Part I of Phase II involved a laboratory evaluation of coatings. Simulation tests were conducted to determine the effect of velocity, humidity, temperature, coating thickness, and contact area on ice friction. From these results, the friction resistance of the hull of an icebreaker was theorized. New materials were also evaluated for possible future use as coatings; and a study of the coating application procedure was conducted. Part II of Phase II was full-scale evaluation of coatings applied to small icebreakers. This was a continuation of testing done in Part II of Phase I. A solventless polyurethane was found to be a good icebreaker hull coating. Part III - under separate cover; is an analysis of icebreaking in particulate (slush) ice. See also report on Phase 1, AD-784 361 and report on Phase 2, Part 3, AD-A024 898.